2021
DOI: 10.1186/s13018-021-02339-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after mini-hook plate fixation for small avulsion fractures around the interphalangeal or metacarpophalangeal joints of the hand

Abstract: Background Mini-hook plate has been described for the treatment of various small avulsion fragments in the hand. This retrospective study aimed to evaluate clinical outcomes after mini-hook plate fixation in patients with an avulsion fracture around the interphalangeal or metacarpophalangeal joints of the hand. Methods Nineteen patients with avulsion fractures around the interphalangeal or metacarpophalangeal joints of the hand were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Hook plate fixation (Teoh and Lee, 2007;Theivendran et al, 2007) has advantages in terms of allowing anatomical reduction, rigid internal fixation, early joint mobilization and avoids pin exposure, which is clearly advantageous for postoperative care. Previous studies (Acar et al, 2015;Lee et al, 2021;Tie et al, 2017;Wang et al, 2021) have reported good to excellent surgical outcomes with DIP flexion of 60 , extension lag 0 as well as good functional scores.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hook plate fixation (Teoh and Lee, 2007;Theivendran et al, 2007) has advantages in terms of allowing anatomical reduction, rigid internal fixation, early joint mobilization and avoids pin exposure, which is clearly advantageous for postoperative care. Previous studies (Acar et al, 2015;Lee et al, 2021;Tie et al, 2017;Wang et al, 2021) have reported good to excellent surgical outcomes with DIP flexion of 60 , extension lag 0 as well as good functional scores.…”
Section: Discussionmentioning
confidence: 90%
“…To date, all rehabilitation protocols have proposed a period of immobilization after surgery. Regimes include immobilization in full extension for 1 week and then allowing mobilization (Acar et al., 2015), 2 weeks of full-time extension immobilization and then passive ROM (Lee et al., 2021; Wang et al., 2021), or full-time splintage for 3 weeks and then active ROM (Tie et al., 2017). The results of our biomechanical studies indicate that it is possible to allow the patient to mobilize the injured finger immediately after surgery using either of the two techniques with an appropriate rehabilitation protocol.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,8,9 Various techniques exist for bony reattachment of the thumb UCL, including pullout suture, 4,5 tension-band wiring 10 and mini-hook plate fixation. 11 The use of suture anchors for thumb UCL repair was first documented thirty years ago, 12 and suture anchor repair has since increased in popularity due to its favourable biomechanical properties, 13 low complication rate 9 (particularly compared with pullout suture 14 ) and the positive clinical outcomes associated with the technique. 8 However, studies reporting outcomes following suture anchor repair are heterogeneous, involving a range of anatomical sites outwith the thumb, 15 a mix of acute and chronic injuries 6,16,17 and the use of supplementary transarticular K-wiring 18 or suture tape augmentation.…”
Section: Introductionmentioning
confidence: 99%